2001
DOI: 10.1046/j.1365-2133.2001.04076.x
|View full text |Cite
|
Sign up to set email alerts
|

The new topical ascomycin derivative SDZ ASM 981 does not induce skin atrophy when applied to normal skin for 4 weeks: a randomized, double-blind controlled study

Abstract: Both topical corticosteroids induced a significant reduction in skin thickness, as compared with SDZ ASM 981 1% cream and vehicle, which were shown to be equivalent. The difference in skin thickness (measured by ultrasound examination) between patients treated with SDZ ASM 981 1% cream and those receiving either of the two topical steroids was significant from day 8 onwards. Histological analysis performed at day 29 showed significant epidermal thinning with topical steroids compared with SDZ ASM 981 1% cream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
139
0
11

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(154 citation statements)
references
References 20 publications
4
139
0
11
Order By: Relevance
“…13,14 As a nonsteroid, pimecrolimus does not induce skin atrophy. 15 Pharmacokinetic studies in adults and pediatric patients with extensive AD lesions have shown negligible absorption of pimecrolimus through the skin, greatly reducing the likelihood of systemic effects after topical application, even in infants with extensive skin lesions. 16 In this study, we evaluated whether early treatment of AD signs and symptoms with pimecrolimus would influence long-term disease outcome by preventing progression to AD flares.…”
mentioning
confidence: 99%
“…13,14 As a nonsteroid, pimecrolimus does not induce skin atrophy. 15 Pharmacokinetic studies in adults and pediatric patients with extensive AD lesions have shown negligible absorption of pimecrolimus through the skin, greatly reducing the likelihood of systemic effects after topical application, even in infants with extensive skin lesions. 16 In this study, we evaluated whether early treatment of AD signs and symptoms with pimecrolimus would influence long-term disease outcome by preventing progression to AD flares.…”
mentioning
confidence: 99%
“…26,27 Unlike TCSs, it does not cause skin atrophy and does not affect the hypothalamic-pituitary-adrenal axis. 26,28 Pimecrolimus cream was developed specifically for the treatment of inflammatory skin diseases, such as AD, allergic contact dermatitis, and chronic irritant hand dermatitis. [29][30][31][32][33][34] The development program for AD involved a large number of infants (defined as subjects Ͻ24 months of age) and children, in recognition of the fact that AD is primarily a pediatric disease.…”
mentioning
confidence: 99%
“…The main reason for developing new drugs as an alternative to topical steroids is to overcome side-effects, such as thinning of the skin and adrenal gland suppression, and recent studies have demonstrated that skin thinning is avoided with the use of pimecrolimus cream 19 . This pilot study demonstrates that pimecrolimus 1% cream as monotherapy was effective in the amelioration of the skin score of patients of DLE, before treatment was 6.78 ± 1.36 and after treatment was 3.97 ± 1.21 (P = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Patients were scheduled for follow-up visits at 2-week intervals. Clinical severity score was determined by assessing three factors including erythema, infiltration and presence of scale (0 = normal; 1 = mild; 2 = moderate; 3 = severe) 2,16,19 . Therefore, by adding the scores given to these three independent criteria, the minimum and maximum clinical scores were 0 (normal skin) and 9 (maximum skin damage), respectively, with mild, moderate and severe disease severity defined as scores of 1-3, 4-6 and 7-9, respectively.…”
Section: Methodsmentioning
confidence: 99%